How to define Celtiberian archaisms? (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2019)
The article defines Celtiberian (CI) archaisms in four different ways:I. CI archaisms correspond to the reconstructed form of one or the other Celtic language.II. CI archaisms are conditioned by the position of CI as one of the Mar- ginal Languages which —in contrast to Gallo-Brittonic as Central-Celtic— have preserved features of earlier Proto-Celtic.III. CI archaisms fall together with the development of linguistic features in east Indo-European (IE) languages including Greek, without being attested in Italic and Germanic.IV. CI archaisms possibly reflect Proto-IE.Every type is illustrated by some examples.